How does plasticity of migration help tumor cells to avoid treatment: Cytoskeletal regulators and potential markers - Alexandrova, Antonina; Lomakina, Maria (Frontiers in Pharmacology, 2022)
Tumor shrinkage as a result of antitumor therapy is not the only and sufficient indicator of treatment success. Cancer progression leads to dissemination of tumor cells and formation of metastases - secondary tumor lesions in distant organs. Metastasis is associated with acquisition of mobile phenotype by tumor cells as a result of EMT and further cell migration based on cytoskeleton reorganization. The main mechanisms of individual cell migration are either mesenchymal, which depends on the activity of small GTPaseRac, actin polymerization, formation of adhesions with extracellular matrix and activity of proteolytic enzymes or amoeboid, which is based on the increase in intracellular pressure caused by the enhancement of actin cortex contractility regulated by Rho-ROCK-MLCKII pathway, and does not depend on the formation of adhesive structures with the matrix, nor on the activity of proteases. The ability of tumor cells to switch from one motility mode to another depending on cell context and environmental conditions, termed migratory plasticity, contributes to the efficiency of dissemination and often allows the cells to avoid the applied treatment. The search for new therapeutic targets among cytoskeletal proteins offers an opportunity to directly influence cell migration. For successful treatment it is important to assess the likelihood of migratory plasticity in a particular tumor. Therefore, the search for specific markers that can indicate a high probability of migratory plasticity is very important.